The Effect of Sustainable Development Objectives and Sustainability Reports on Profitability with Company Size as a Moderating Variable in Companies Listed on the Indonesia Stock Exchange in 2019-2024 - Dimas Septianto; Herman Ruslim (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Sustainable Development Goals and Sustainability Reports on Profitability, and to test the role of the Company Size variable as a moderating variable. This study was conducted on all companies listed on the Indonesia Stock Exchange from 2019-2024. The sampling technique used in this study was purposive sampling. The analysis method in this study was panel data regression analysis and Moderated Regression Analysis. The results of the study showed that Sustainable Development Goals did not affect Profitability, in contrast to Sustainability Reports, which actually had a significant positive effect on Profitability. Company Size succeeded in strengthening the positive effect of Sustainability Reports on Profitability, and failed to moderate the Sustainable Development Goals variable.